The Transformation of the Refund Provisions of Tabarru’ in Islamic Insurance: Fatwa DSN-MUI No. 53/2006 and No. 81/2011 - Fitriansyah, Helmi; Rukmini, Neng Vivie Nurfauziah; Al Hakim, Sofian (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2025)
This article examines the management of Tabarru’ funds in Islamic insurance by analyzing Fatwa DSN-MUI No. 53/2006 and No. 81/2011, which play a crucial role in addressing operational and legal challenges within the Islamic insurance industry. The background of this study highlights legal uncertainties surrounding the status of Tabarru’ funds, which are defined as non-refundable grants in Fatwa No. 53/2006. In contrast, Fatwa No. 81/2011 introduces flexibility by allowing partial refunds for participants who terminate their contracts early, adapting to market needs. This study employs a normative juridical approach, involving a comprehensive analysis of primary and secondary legal texts, including fatwas DSN-MUI, Islamic legal literature, and case studies on the implementation of these fatwas in the practice of Islamic insurance in Indonesia. The findings indicate that Fatwa No. 81/2011 significantly contributes to the management of Tabarru’ funds by introducing flexibility in refunding participants. The fatwas concerning Tabarru’ funds in Islamic insurance demonstrate that they complement each other in regulating the concept and management of these funds. The operational implications of this study include recommendations to strengthen regulations and transparency in the management of Tabarru’ funds and to enhance the protection of participants' rights.